Amygdalin Attenuates Atherosclerosis and Plays an Anti-Inflammatory Role in ApoE Knock-Out Mice and Bone Marrow-Derived Macrophages - Wang, Yiru; Jia, Qingyun; Zhang, Yifan; Wei, Jing; Liu, Ping (Frontiers in Pharmacology, 2020)
Amygdalin, the main component of Prunus persica (L.) Stokes, has been used to treat atherosclerosis in mouse model due to its anti-inflammatory role. However, the exact mechanism underlying its protective property remains poorly understood. This study aimed to evidence the influence of amygdalin on high-fat diet induced atherosclerosis in ApoE knock-out (ApoE-/-) mice, and unravel its anti-inflammatory mechanism. ApoE-/- mice fed with HFD for eight weeks were randomly divided into four groups and injected with amygdalin at the concentration of 0.08 mg/ kg or 0.04 mg/ kg for twelve weeks. Additionally, bone marrow-derived macrophages were intervened with oxidized low-density lipoprotein (oxLDL) or lipopolysaccharide plus various concentrations of amygdalin for further exploration. Body weight, serum lipid profiles and inflammatory cytokines were detected by ELISA, gene expression by RT-PCR, plaque sizes by Oil Red O, lymphatic vessels of heart atrium and TNF- production by immunofluorescence staining. MAPKs, AP-1 and NF-B p65 pathways were also explored. Amygdalin decreased ApoE-/- mice body weight, serum lipids, plaque size, lymphatic vessels and inflammatory cytokines (IL-6, TNF-), NO and iNOS, and increased IL-10 expression. In oxLDL-induced bone marrow-derived macrophages, amygdalin reduced inflammatory cytokines (IL-6, TNF-), NO and iNOS, and increased IL-10 production. These effects were associated with the decrease of phosphorylated ERK1/2, JNK, p38, c-Fos and c-Jun, and the translocation of NF-B p65 from nucleus to cytoplasm. These results suggested that amygdalin could attenuate atherosclerosis and play an anti-inflammatory role via MAPKs, AP-1 and NF-B p65 signaling pathways in ApoE-/- mice and oxLDL-treated bone marrow-derived macrophages.